Isu Hak Konstitusional Masyarakat Desa Terhadap Kewenangan Pengawasan Pemilihan Kepala Desa - Supriyadi Arief; Rahmat Teguh Santoso Gobel (The Constitutional Court of the Republic of Indonesia, 2022)
The election of village heads (Pilkades) is the representation of democracy at the village level. Nevertheless, the supervision mechanism by the district/city level election committee (PPK) becomes problematic when the authority also coincides with the authority to operate. It is important to know the legal construction regarding the supervision of village head elections and the model of village head election supervision in the future. These will be analyzed normatively using a statutory approach, case approach, and concept approach. The results of this study show that Pilkades is an important process to actualize the Constitutional rights of communities, democracy and village autonomy. However, the regulations governing the pilkades are not in line with democratic values and the principle of free and fair election because of the unification of the authority to operate and supervise simultaneously at the Village Head Election Committee formed by the regional Head. Therefore, improvements to the supervision of the Pilkades in the future can be carried out with three models, namely: involving district/city Bawaslu, forming district/city Pilakdes Supervisors, direct supervision by district/city Bawaslu.